Daniellia oliveri as a type 2 diabetes remedy: evidence from in-silico evaluation - Adeyemi, Sherif Babatunde; Saliu, Ahmed Abiodun; Joshi, Bhrugesh Pravinchandra; Krishnamurthy, Ramar (Taylor and Francis, 2024)
The prevalence of diabetes mellitus is increasing, and well-known conventional medications are associated with harmful effects. Therefore, this study aimed to identify the compounds present in the young leaves of Daniellia oliveri and assess their antidiabetic potential using an in-silico model. The best column chromatographic fraction obtained from ethyl acetate fraction was analyzed using HRLC-MS to identify the prominent compounds. The identified compounds were subjected to ADMET prediction using online servers to confirm their draggability. In addition, the compounds were screened for activity against type 2 diabetes using molecular docking. Eight compounds with prominent peaks were identified, viz; gallic acid, 2,6-dihydroxybenzoic acid, salicylic acid, caffeic acid, phenylacetaldehyde, 2,5-dimethylphenol, 3-(−4-Hydroxyphenyl) propionic acid, and 16-hydroxyhexadecanoic acid. Most of the identified compounds were phenolics and had little toxic effects. The molecular docking results revealed the potentials of the identified compounds in inhibiting the therapeutic targets viz; 11β-hydroxysteroid dehydrogenase type 1, human salivary alpha-amylase, glycogen phosphorylase, human protein tyrosine phosphatase 1B, glutamine fructose-6-phosphate amidotransferase, human sirtuin 6, and dipeptidyl peptidase IV, responsible for the development of type 2 diabetes. This study has successfully revalidated and provided scientific insight into the usage of D. oliveri in managing type 2 diabetes by Nigerians. However, the limitation of this study remains the purification of the lead compounds that can serve as lead for type 2 diabetes treatment in conventional medicinal practices.